The epidemic of wheat stem rust (Puccinia graminis tritici) on spring wheat in South-West Finland in 1951, primarily from the breeder’s point of view - Kivi, Erkki I. (Agricultural and Food Science, 1956)
The paper reports on the black stem rust epidemic in South-West Finland in summer 1951, primarily from a plant breeder’s point of view. The report is based on the material collected by the Agricultural Research Centre, Department of Plant Breeding, from the spring wheat cultivations of South-West Finland and the Department’s trial field at Jokioinen. 1. Black stem rust was quite general in spring wheat throughout the southwest of Finland. In the extreme south-western part of the country the crop losses caused by drought and black stem rust were up to and over 50 per cent. In the eastern district of the area under review the damage by black stem rust was negligible in spite of heavy infection. 2. The coefficient of the correlation between the amount of black stem rust and 1,000 grain weight in the material collected from farms was —0.77 ± 0.04, and in a material obtained from the trial field —0.81 ± 0.05. 3. All the varieties grown in South-West Finland were susceptible to black stem rust. Kärn II, Diamant and Diamant II showed practically the same degree of infection. Thanks to its early ripening, the early Apu wheat in certain cases avoided heavy black stem rust infection. 4. On the trial field the north European varieties proved definitely more susceptible than many of the American varieties. Black stem rust was the most widespread of the wheat rusts in summer 1951 (cf. Table 3). 5. The younger breeding material revealed clearly the general susceptibility to black stem rust of the origins. It also showed the favourable effect on the descendants of the resistant parent strains employed in certain crosses. 6. A study of the origins of the Finnish varieties showed that hardly any varieties resistant to black stem rust have been employed as parents for our present commercial varieties.